2003
DOI: 10.1073/pnas.0537194100
|View full text |Cite
|
Sign up to set email alerts
|

A rhodium(III) complex for high-affinity DNA base-pair mismatch recognition

Abstract: A rhodium(III) complex, rac-[Rh(bpy)2phzi] 3؉ (bpy, 2,2-bipyridine; phzi, benzo[a]phenazine-5,6-quinone diimine) has been designed as a sterically demanding intercalator targeted to destabilized mismatched sites in double-helical DNA. The complex is readily synthesized by condensation of the phenazine quinone with the corresponding diammine complex. Upon photoactivation, the complex promotes direct strand scission at singlebase mismatch sites within the DNA duplex. As with the parent mismatch-specific reagent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
97
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 19 publications
1
97
0
1
Order By: Relevance
“…Measurements of the abundance of mismatches provides an early report on deficiencies in mismatch repair. 9 Towards that end, we have developed luminescent analogues as probes for mismatches. 10,11 Bifunctional complexes have also been designed to target alkylators and platinating agents to mismatched sites.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the abundance of mismatches provides an early report on deficiencies in mismatch repair. 9 Towards that end, we have developed luminescent analogues as probes for mismatches. 10,11 Bifunctional complexes have also been designed to target alkylators and platinating agents to mismatched sites.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mutations in MMR genes have been identified in 80% of hereditary non-polyposis colon cancers, and 15-20% of biopsied solid tumors have shown evidence of somatic mutations associated with MMR [10][11][12] . Mismatch detection may provide an early indicator of these cancerous transformations 13 .…”
Section: Introductionmentioning
confidence: 99%
“…2) 3,13 . The preparation of the simplest complexes in each family, Rh(bpy) 2 (chrysi) 3+ and Rh(bpy) 2 (phzi) 3+ , is described here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any characteristic or state that distinguishes the neoplastic cell may represent a potential target, especially if it is not easily modifiable by the tumor cell during the process of growth and evolution either in the absence or presence of therapy. We and others have previously suggested that defective nucleotide mismatch recognition and repair (MMR) could be one such state (3,4). Another targetable and relatively irreversible cellular state might be the complexity and instability of the chromosomal complement of cancer cells.…”
mentioning
confidence: 99%